Teacher’s Perception of Antisocial Behaviours and Academic Achievement of Secondary School Students in Obollo-Afor Education Zone - Eze, Jude U.; Mamah, Miriam I; Nwankwo, Evangeline U. (International Journal of Human Kinetics, Health and Education, 2022)
The growing rate of poor academic achievement of secondary school students has been partly deduced to antisocial behaviour. The study assessed teachers' perception of antisocial behaviours and academic achievement of secondary school students in Obollo-Afor Education Zone. Two research questions and two null hypotheses were formulated and posed to guide the study. The study adopted a descriptive cross-sectional survey research design. 1,574 teachers (males 477 and females 1,097) in all the 46 secondary schools in Obollo-Afor Education Zone formed the target population for the study. A sample of 315 (82 male and 232 female) teachers was used for the study. A questionnaire titled "Teachers' Perception of Antisocial Behaviour on Students' Academic Achievement Questionnaire (TPABSAAQ)" was used for data collection. Three experts face-validated the instrument. Cronbach’s Alpha was used to determine the internal consistency of the questionnaire items and reliability coefficients of 0.81, 0.78 for clusters A and B respectively were obtained. Data collected were analyzed using mean, standard deviation, and t-test at 0.05 level of significance. The results revealed, among others, that truancy and drug abuse as perceived by teachers affect students' academic achievement. The results also revealed that there is no significant difference between the mean responses of male and female teachers' perception of these variables on academic achievement of secondary school students in Obollo-Afor Education Zone. However, there is a need for enlightenment campaigns by government and non-government organizations/ agencies for parents and children on the dangers inherent in truancy and drug abuse.